Optimizing Bio-Oil Yield: A Study on Trichosanthes Tricuspidata Seed Extraction - V. Mansa Devi; M. Dharmendira Kumar; R. Sridhar; C. Jaya Kumar (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
This study investigates Trichosanthes tricuspidata seeds as a potential novel source for bio-oil production. Employing a Soxhlet extractor, the research delves into the presence of fatty acids in oil extracted using various solvents. The primary aim is to optimize the extraction process to maximize bio-oil yield, examining factors such as extraction time and seed particle size. Initial experiments encompass a diverse range of particle sizes and extraction durations. Subsequently, to refine the process, a fixed particle size is utilized alongside different solvents. The study identifies the optimal extraction process as a 3h extraction time with a particle size of 0.55 mm, employing isopropyl alcohol as the solvent, resulting in a bio-oil extraction rate of 20% (w/w). The significance of this research lies in introducing a fresh approach to bio-oil production from an untapped plant source. By enhancing the extraction process from Trichosanthes tricuspidata seeds, this study contributes to the advancement of sustainable and economically viable bio-oil production methods. Furthermore, the study employs analytical techniques to comprehend the composition of the extracted bio-oil.